Welsh writing, political action and incarceration Branwen's Starling - Mac Giolla Chriost, Diarmait 1965- (Palgrave studies in minority languages and communities, 2013)
"Welsh Writing, Political Action and Incarceration examines the prison literature of certain iconic Welsh authors whose political lives and creative writings are linked to ideas about Wales and the Welsh language. Through this case study, the author interrogates the nature of political activism and social movements, including the use of violence and non-violent approaches to protest. Also examined are the function and significance of variations in literary form, style and language in this prison literature along with the motivations driving each of these prison authors and the effects of their texts on their readers - their community outside of prison, and upon society more widely. This work successfully challenges orthodox perspectives on this body of prison literature. In adopting a case study approach the author universalizes the Welsh experience, drawing insights from international research on prison literature, the political science of protest and the sociology of language"--